PENGARUH ADVERSITY QUOTIENT TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS NEGERI 2 SIAK HULU - Mia Salmiah (UIR Press, 2021)
This research aims to get information about how big the effect adversity quotient toward Student’s Learning Motivation in Economics at the Sttate Senior High School of 2 Siak Hulu. The background of the research were some student cheated in doing their tasks, they did not submit their assignment on time, they did not bring their economics textbooks, and they did not study seriously. This was a quantitative research. The subject of this research was the eleventh grade students whose major were sosial science. The object of this research was the effect adversity quotient to word students’s learning motivation. The number of sample of this research were 127 students. The research used random sampling technique. The data collection technique used was questionares and documentations. This technique of analysis used to examine the hypothesis was simple linier regression. Based on the result of the research and data analysis, it was found that ro (observasi) 0,688 bigger than rt (tabel) with the level of sifnificance 5% (0,1743) and 1% (0,2278) at (0,1743<0,688>0,2278) or that there is a significant effect of adversity quotient toword students’ learning motivation in economics at the State Senior High School of 2 Siak Hulu. The percentage of adversity quotient effect toward students’ learning motivation was 47,3% while the rest 52,7% was influenced by other variables which were not included in this research.